Reseña/Review (Gehl, R., "Reverse engineering social media: software, culture and political economy in new media capitalism", Philadelphia, PA: Temple University Press, ISBN 978 1 43991 035 1, 236 págs., 2014) - de Rivera, Javier (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
Reseña/Review (Gehl, R., "Reverse engineering social media: software, culture and political economy in new media capitalism", Philadelphia, PA: Temple University Press, ISBN 978-1-43991-035-1, 236 págs., 2014)